PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI BALAI PENGELOLA KERETA API RINGAN SUMATERA SELATAN - Anjel, Anjel; Maliah, Maliah; Usman, Benny (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of compensation and motivation on employee job satisfaction. The method used in this study is a quantitative method with the number of samples studied were 41 respondents. The data analysis techniques used in this study are multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-test, and F-test using the SPSS 26 program. The results of the study can be concluded that partially and simultaneously there is a significant influence between compensation and motivation variables on work satisfaction at the Riangan Railway Management Center of South Sumatra. Keywords: Compelnsation; Motivation; Job Satisfaction